The Stigma Reduction in Tuberculosis (TB) to Increasing TB Case Detection Among Women's Communy in Abepura, Papua: Stigma Reduction in Women's Community in Abepura- Papua to Increase Tuberculosis (TB) Case Detection - Sianturi, Elfride Irawati; Gunawan, Elsye; Appa, Felycitae Ekalaya; Soltief, Sitti Nurdjaja; Suthelie, Chinry Charolina; Febriyanti, Christine; Rusnaeni, Rusnaeni (Sam Ratulangi University, 2025)
Papua Province is one of the regions with the highest number of tuberculosis cases, and this is a serious problem for the province and the surrounding area. The most significant impact of this disease on the community is a decline in quality of life and health status. Although patient care, evaluation of new treatments, and tuberculosis prevention strategies are constantly being updated, tuberculosis remains the leading cause of morbidity. The shame people feel around tuberculosis makes it hard to control the disease. TB patients are more likely to conceal their condition, which leads to delayed detection and increased transmission. The objective of this initiative is to enhance the involvement of women's groups in the region in recognizing TB symptoms and mitigating the stigma surrounding TB. The methods used were counseling and testimonials from TB patients who had recovered. The activity was participated in by a total of 19 women, and their stigma was observed before and after the activity. The results showed a tendency for significant change if this activity was carried out regularly, with the reduction in stigma leading to the community actively supporting early detection of TB when they saw symptoms of the disease without fear of being stigmatized by TB. ABSTRAK Provinsi Papua merupakan salah satu wilayah dengan kasus TBC tertinggi. Dampak yang paling dirasakan oleh masyarakat mengenai penyakit ini yakni terjadinya penurunan kualitas hidup dan status kesehatan. Meskipun perawatan pasien, evaluasi terhadap perawatan baru atau strategi pencegahan TBC selalu diperbaharui tetapi TBC masih menjadi penyebab utama morbiditas. Stigma yang memiliki keterkaitan pada TBC menghambat keseluruhan dari aspek yang terkait dengan pengendaliannya TBC. Para pasien yang terkena TBC jauh lebih cenderung untuk menyembunyikannya kondisi yang sedang mereka alami dan hal ini mengakibatkan keterhambatan pendeteksian kasus hingga membuat terjadinya penularan yang lebih meluas. Tujuan kegiatan ini adalah meningkatkan partisipasi kelompok wanita di daerah tersebut mampu mengenali gejala TBC serta pengurangan stigma terhadap TBC dapat dikurangi. Metode yang dilakukan adalah penyuluhan dan testimoni pasien TBC yang sudah sembuh. Sebanyak 19 perempuan mengikuti kegiatan ini dengan melihat stigma mereka sebelum dan sesudah kegiatan. Hasil yang didapat bahwa adanya kecenderungan akan adanya perubahan secara signifikan bila kegiatan ini rutin dilakukan sehingga pengurangan stigma ini akan menyebabkan Masyarakat secara aktif mendukung pendeteksian dini TBC Ketika melihat simptom dari penyakit ini tanpa takut akan distigmatisasi.